The Natural Resources and the relation with the Environmental Accounting in Perú - Quispe Cornejo, Silvia Consuelo (2010)
This investigation try to explain the limitations about to count the loss of natural capital or the natural resources like the woods, petroleum, minerals, gas. One of the alternatives to cover these deficiencies is to elaborate an System of Environmental Accounting and Integral Economy, that provide us a new conceptual mark and a common methodology, for the development of the economic information and environmental that require Perú, in others words, a System of National Economic Integral Accounting. The actual system of the National Bills, don’t show the reality to use the natural resources like capital natural, knowing that the raw material is the principal element in the production of the diversity economics activities, but it isn’t count like depreciation, this constitute a system of incomplete measurement that not consider the destruction of the natural capital and how we know the nature loss little by little the natural resources, these resources are exhausted or degradated, and don’t exist none compensation, that give us a future protection